Conductive bridge resistive random access memory (CBRAM) - Chua, Wei Liang (Nanyang Technological University, 2024)
Modern computer architecture incorporates three principal memory technologies: DRAM, SRAM, and Flash memory. However, due to the scaling limitation of charge-based memory technologies, emerging memory technologies are looking to replace these conventional memory technologies by introducing a new storage class memory (SCM). It combines the high speed and endurance characteristics of DRAM with the non-volatility of Flash Memory, which is urgently needed to fulfill the computing needs of this internet-of-things era. Conductive bridge random access memory (CBRAM) stands out as one of the most promising candidates for future memory technology, which relies on the migration of metal ions and subsequent redox reactions. Its appeal lies in its low operating voltage, minimal energy consumption, exceptional scalability, large memory window, and versatile switching characteristics.